2014
DOI: 10.1002/cam4.344
|View full text |Cite
|
Sign up to set email alerts
|

G‐CSF utilization rate and prescribing patterns in United States: associations between physician and patient factors and GCSF use

Abstract: Febrile neutropenia (FN) is a common complication among patients with chemotherapy-induced myelotoxicity and is associated with a number of negative outcomes including prolonged hospitalization, increased medical costs, increased risk of mortality, dose reductions, and delays. Granulocyte-colony-stimulating factor (G-CSF), granulocyte–macrophage-colony stimulating factor (GM-CSF), and pegylated G-CSF are effective at reducing risk and duration of neutropenia-related events. However, despite guidelines, the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 47 publications
4
40
1
1
Order By: Relevance
“…Another study found that G-CSFs was being over utilized in patients undergoing chemotherapy associated with low risk of FN and underutilized in patients with high risk of FN. This finding is similar to ours, whereby G-CSFs were underutilized in patients with high risk of FN [17][18][19][20][21][22][23][24][25]. However, G-CSFs were prescribed appropriately in intermediate-and low-risk patients at our institution.…”
Section: Discussionsupporting
confidence: 89%
“…Another study found that G-CSFs was being over utilized in patients undergoing chemotherapy associated with low risk of FN and underutilized in patients with high risk of FN. This finding is similar to ours, whereby G-CSFs were underutilized in patients with high risk of FN [17][18][19][20][21][22][23][24][25]. However, G-CSFs were prescribed appropriately in intermediate-and low-risk patients at our institution.…”
Section: Discussionsupporting
confidence: 89%
“…Patient adherence with the filgrastim regimen is another potentially salient reason for under-dosing. Lack of physician familiarity or awareness of the G-CSF guidelines and/or the consequences of FN on RDI and, thereby, cancer survival is likely to be another factor behind under-dosing of filgrastim and under use of G-CSF in general [39][40][41]. In Germany, for example, despite 85.1% of 195 physicians stating that they followed G-CSF guidelines, evidence revealed only 15.4% adherence for high-risk lung cancer patients and < 50% for intermediaterisk lung and breast cancer patients [41].…”
Section: Pegfilgrastim Versus Filgrastimmentioning
confidence: 99%
“…Lack of risk factors was cited by over half the physicians as a reason for not using G-CSF in patients prescribed a chemotherapy with a FN risk ≥ 20% [41], yet the assessment of risk factors in this group of patients is unnecessary and only required for intermediate-or low-risk groups [1,5,16]. Overall, it has been reported that as many as 80% of patients do not receive primary prophylaxis with G-CSF in accordance with their assessed risk [39,41]. Dose reductions of chemotherapy related to neutropenia and use of G-CSF only as secondary prophylaxis have also been found to be widespread in clinical practice [39,41].…”
Section: Pegfilgrastim Versus Filgrastimmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey questionnaire was developed using standard survey methodology [22]. Before online implementation, a draft survey questionnaire was reviewed in two pilot tests.…”
Section: Survey Developmentmentioning
confidence: 99%